Pyroelectric power generation with ferroelectrics (1-x)PMN-xPT. (19th May 2017) - Kim, Juyoung; Yamanaka, Satoru; Nakajima, Akira; Katou, Takanori; Kim, Yoonho; Fukuda, Tatsuo; Yoshii, Kenji; Nishihata, Yasuo; Baba, Masaaki; Takeda, Masatoshi; Yamada, Noboru; Nakayama, Tadachika; et al.
ABSTRACT: A novel electrothermodynamic cycle based on temporal temperature variations (dT/dt); the pyroelectric effect was investigated for its potential role in the use of waste heat as renewable energy. Here, we present improved generating performance with relaxer ferroelectric ceramics ((1- x )Pb(Mg2/3 Nb1/3 )O3 - x PbTiO3 (PMN- x PT)), which are well known for their strong dielectric and pyroelectric properties near the morphotropic phase boundary. The theoretical potential was evaluated using hysteresis loops, and the generating properties were analyzed in the laboratory using an engine dynamometer. The experiments yielded a value of 0.48 mW/cm 3, which is 3 times larger than that obtained previously, because of the high polarization properties.